2021
DOI: 10.1017/pasa.2021.38
|View full text |Cite
|
Sign up to set email alerts
|

A broadband radio view of transient jet ejecta in the black hole candidate X-ray binary MAXI J1535–571

Abstract: We present a broadband radio study of the transient jets ejected from the black hole candidate X-ray binary MAXI J1535–571, which underwent a prolonged outburst beginning on 2017 September 2. We monitored MAXI J1535–571 with the Murchison Widefield Array (MWA) at frequencies from 119 to 186 MHz over six epochs from 2017 September 20 to 2017 October 14. The source was quasi-simultaneously observed over the frequency range 0.84–19 GHz by UTMOST (the Upgraded Molonglo Observatory Synthesis Telescope) the Australi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Based on our results and the radio measurements of Russell et al (2019) and Chauhan et al (2021), in Figure 6, we present schematically a possible scenario of the evolution of the X-ray corona and the simultaneous radio jet. The parameters from the reflection suggest a rather stable inner radius of the disc that is very close to the ISCO, so the disc inner radius does not change significantly in Figure 6.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Based on our results and the radio measurements of Russell et al (2019) and Chauhan et al (2021), in Figure 6, we present schematically a possible scenario of the evolution of the X-ray corona and the simultaneous radio jet. The parameters from the reflection suggest a rather stable inner radius of the disc that is very close to the ISCO, so the disc inner radius does not change significantly in Figure 6.…”
Section: Discussionmentioning
confidence: 74%
“…Our results of the temporal evolution of the corona may be compared to the evolution of the radio jet detected in this source. Radio measurements (Russell et al 2019(Russell et al , 2020Chauhan et al 2021) show that during the intermediate state of MAXI J1535−571 a steady, optically thick jet gradually quenches and then changes into a transient jet. More specifically, on MJD 58008, the radio observations detect a steady, optically thick jet.…”
Section: Discussionmentioning
confidence: 99%
“…Jet opening angles have only been constrained for a number of black hole X-ray binaries (see e.g. Stirling et al 2001;Miller-Jones et al 2006;Rushton et al 2017;Tetarenko et al 2017;Tetarenko et al 2019b;Espinasse et al 2020;Chauhan et al 2021;Tetarenko et al 2021). Measurements of jet opening angles range from 0.4−1.8°in the compact jet of Cygnus X-1 (Tetarenko et al 2019b) to ∼ 58°i n XTE J1908+094 (Rushton et al 2017), although we note that Rushton et al (2017) suggested that this number is derived from the lateral expansion of the jet lobe and thus the jet opening angle is likely smaller.…”
Section: Jet Kinematicsmentioning
confidence: 90%
“…Results from radio have mainly explored the transient behavior of the jet and/or the relationship between the jet and accretion disk (Parikh et al 2019;Russell et al 2019Russell et al , 2020Chauhan et al 2021). Chauhan et al (2019) used radio observations to determine the distance to the source (∼4 kpc).…”
Section: Introductionmentioning
confidence: 99%